If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 = 5x + -15 Reorder the terms: 40 = -15 + 5x Solving 40 = -15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 40 + -5x = -15 + 5x + -5x Combine like terms: 5x + -5x = 0 40 + -5x = -15 + 0 40 + -5x = -15 Add '-40' to each side of the equation. 40 + -40 + -5x = -15 + -40 Combine like terms: 40 + -40 = 0 0 + -5x = -15 + -40 -5x = -15 + -40 Combine like terms: -15 + -40 = -55 -5x = -55 Divide each side by '-5'. x = 11 Simplifying x = 11
| 8.4m-0.7-8m=0.22 | | 7x+10=2x-10 | | 2gh+5h-20-8g= | | 4(9.7-8.1)=4(9.7)-4(8.1) | | 5/6(9+2x)=40 | | -.5-1=15 | | 2gh-12h-5g+30= | | 12s+8=4s-2 | | .75p-0.6p= | | 4x^2-20x+23=0 | | 3y-7/5=16 | | 8x+15=3x-15 | | 16+x=y | | 2g-5= | | 0.8z+3.74=z+1.5 | | 4(9.7-8.1)=(9.7)-(8.1) | | 75=3-10t-3+6t | | .75(x-5)=12 | | .5x+1=.5x-1 | | .75w-.50w-4=12 | | 8(x+2)=2(4x+4)+8 | | (-3a^2b^3)(-4a^4b^2)= | | 3(t-1)=9+2 | | 596=-8x | | .75(x+5)=12 | | -9x-21=35x | | m-1=-2-9 | | 5w^2-23w-42=0 | | s=L-rL | | 2x-36=5(x+3) | | 100=20t+5t^2 | | 4-5X=59 |